The Significance of Advanced Mathematics in Secondary and Higher Education - Hiya Bhasin, (European Economic Letters (EEL), 2023)
Learning advanced mathematics in high school or college offers a myriad of benefits to students in academic, personal, and professional pursuits as it presents them with the opportunity to engage in critical, abstract, and logical thinking. By tackling complex problems, students enhance their cognitive abilities, learning to dissect intricate issues into manageable components and devise coherent strategies to resolve them. This process of reasoning and problem-solving fosters brain development and elevates overall cognitive skills. The present study delves into the advantages of learning advanced mathematics in high school or college.